Weak Type Weighted Inequalities for the Commutators of the Multilinear Calderón-Zygmund Operators (Analysis in Theory and Applications, 2017)
For the commutators of multilinear Calderón-Zygmund singular integraloperators with BMO functions, the weak type weighted norm inequalities with respectto $A_{\vec{p}}$ weights are obtained.
Keywords: Commutator; multilinear Calderόn-Zygmund operator; multilinear maximal function; weight.